Time-resolved luminescent spectrometry of zink selenide crystals - Oleshko, V.I.; Vil’chinskaya, S.S.; Gorina, S.G. (Publishing House of the KarSU named after E.A.Buketov, 2011)
The spectral and kinetic characteristics of pulse cathodoluminescence of undoped ZnSe single-crystals grown by sublimation from the vapor phase (Davydov-Markov method) and by flux growth (Bridgman method) have been measured. Three groups of bands were found in the spectra of radiative recombination of zinc selenide: exciton, edge emission and bands due to the recombination of carriers in deep centers. The spectral-kinetic characteristics of the edge emission in ZnSe crystals with different previous history have been studied. It was found that the number of edge emission series, the ratio of their intensities and spectral position are to be determined by the previous history of crystals. It is shown that the total intensity of the edge emission reduces more than tenfold with the temperature increase in the range of 15 - 80 K. The results obtained show that the properties of the edge emission can be well described by the model of donor-acceptor pairs.
Keywords: cathodoluminescence; sublimation; single-crystals; edge emission; radiative recombination